Increasing Phenol Levels in Liquid Smoke as an Antimicrobial from the Pyrolysis Results of Tobacco Stem Waste Using Distillation and Adsorption Methods - Rasendriya Putra Reswara; Annisa Mutiara Salma Haque; Anita Ristikawati; Dimas Nur Arifianto; Ika Nawang Puspitawati (Future Science, 2023)
Liquid smoke is obtained from the condensation of smoke resulting from burning biomass during the pyrolysis method. Biomass that can be used in the process of forming liquid smoke has the characteristics of containing cellulose and lignin. Liquid smoke contains ingredients that can be used as antimicrobial substances, namely phenolic compounds. The method that can be used to increase the phenol content in liquid smoke is the adsorption and distillation method. This research aims to increase the phenol content in the liquid smoke with a stage I purification process, namely, adsorption using an activated carbon adsorbent, and stage II purification, namely distillation at a temperature of 120 °C. The variables used in the research are variations in pyrolysis time (250°C, 300°C, and 350°C) and pyrolysis time (1 hour, 1.5 hours, and 2 hours). The results showed that liquid smoke experienced changes in the amount of phenol content. The highest phenol content obtained occurred at a variable temperature of 350 °C over 2 hours, amounting to 23.10 ppm, and increased after adsorption and distillation to 27.20 ppm. Changes in pH, density, and color in liquid smoke occur after distillation and adsorption, where the highest pH is 4.9, the lowest is 3.7, the highest density value is 1.011 gr/ml, and the lowest is 0.993 gr/ml.